Patient-reported adverse events under asthma therapy: a community pharmacy-based survey. - Laforest, L; Van Ganse, E; Devouassoux, G; Osman, L; Bauguil, G; Chamba, G (2007)
The characteristics of patients who report adverse events (AEs) attributed to asthma therapy have been little investigated. Asthma patients aged 18-50 years were surveyed in pharmacies. Patients completed a questionnaire linked to computerized records of dispensed medications. Patients reported all AEs that they attributed to asthma therapy. The correlates of reporting 2+ AEs were identified. Almost 59% of the 1,351 patients (mean age: 37, 56% females) attributed AEs to asthma therapy, and 35% at least two. Most common AEs included tiredness (21.8%) and palpitations (21.1%). Poor asthma control and perception of asthma as a handicap were the major correlates of reporting 2+ AEs (odds ratio (OR)=2.5, 95% confidence interval (CI)=[1.7-3.7] and OR=1.9, 95% CI=[1.4-2.5]). Other significant correlates included age >30 years, female gender, and receiving psychotropic therapy. Inadequate control may partly account for AEs attributed by patients to asthma therapy. Improving patients' education may help to improve acceptability of asthma therapy.